The Eternals the dreaming celestial saga - Gillis, Peter B. 1952-2024; Simonson, Walter 1946-; Stern, Roger 1950- (Marvel Worldwide Inc., 2020)
"A thread from the deviants rises to unleash the power of the dreaming celestial!" -- back of cover